2014
DOI: 10.11646/phytotaxa.174.5.3
|View full text |Cite
|
Sign up to set email alerts
|

Rafflesia mixta (Rafflesiaceae), a new species from Surigao del Norte, Mindanao, Philippines

Abstract: Rafflesia mixta Barcelona, Manting, Arbolonio, Caballero & Pelser is described as a new species from the Caraga Region of northeastern Mindanao, Philippines. In their general morphology, the flowers of this species most closely resemble those of R. mira, but they are different in details of the perigone warts and processes, disk color, and relative size of the diaphragm opening. This discovery brings the total number of Philippine Rafflesia species to twelve, of which four are found on the island of Mindan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…(Nais, 2001). Rafflesia has recently been the focus of several research projects in which new species were discovered and described (e.g., Barcelona & al., 2009bBarcelona & al., , 2014Balete & al., 2010;Mat-Salleh & al., 2010;Galindon & al., 2016). Molecular phylogenetic studies further revealed that Rafflesia mitochondria contain DNA regions that were obtained from Tetrastigma through horizontal gene transfer (Davis & Wurdack, 2004) and that some of these genes are expressed by the parasite (Xi & al., 2012).…”
Section: Version Of Recordmentioning
confidence: 99%
See 1 more Smart Citation
“…(Nais, 2001). Rafflesia has recently been the focus of several research projects in which new species were discovered and described (e.g., Barcelona & al., 2009bBarcelona & al., , 2014Balete & al., 2010;Mat-Salleh & al., 2010;Galindon & al., 2016). Molecular phylogenetic studies further revealed that Rafflesia mitochondria contain DNA regions that were obtained from Tetrastigma through horizontal gene transfer (Davis & Wurdack, 2004) and that some of these genes are expressed by the parasite (Xi & al., 2012).…”
Section: Version Of Recordmentioning
confidence: 99%
“…In this study, we aim to contribute to knowledge of the evolution of the host-parasite associations between Tetrastigma and Rafflesia and the conservation of Rafflesia in the Philippines by determining patterns of host specificity and preference. The Philippine archipelago is home to 13 currently recognized Rafflesia species (Barcelona & al., 2014;Galindon & al., 2016), all of which are endemic to the country. A total of 11 Rafflesia species were included in our studies and their hosts were collected throughout their distribution range and in most areas from which Rafflesia is presently known.…”
Section: Version Of Recordmentioning
confidence: 99%
“…Male and female flowers are found in different individuals [2,3]. Rafflesia lives as holoparasite [3,4,5] and attached to the host plant through an organ called haustoria which has a root-like function [1]. The host belongs to the genus Tetrastigma (Vitaceae) which is liana [6].…”
Section: Introductionmentioning
confidence: 99%
“…(Rafflesiaceae) is a genus of endophytic, holoparasitic plants, well-known for producing the largest flowers on record (Kuijt 1969, Meijer 1985, 1997, Nais 2001). The Philippines is one of the centers of diversity of the genus (Barcelona et al 2009b, Pelser et al 2013), with at least 12 species thus far recorded from the archipelago (Teschemacher 1842, Blanco 1845, Hieronymus 1885, Barcelona and Fernando 2002, Fernando and Ong 2005, Barcelona et al 2006, 2008a, 2008b, 2009a, 2009b, 2011, 2014, Galang and Madulid 2006, Balete et al 2010, Pelser et al 2013), eight of which were described only since 2002. Of all known Philippine species, five are recorded from Luzon Island, viz., Rafflesia aurantia Barcelona, Co & Balete (Barcelona et al 2009a) from Quirino Province; Rafflesia baletei Barcelona & Cajano (Barcelona et al 2006) from Camarines Sur Province; Rafflesia lagascae Blanco (Blanco 1845, Barcelona et al 2009, 2011 [as Rafflesia manillana Teschem.…”
Section: Introductionmentioning
confidence: 99%